Odonata diversity (Insecta: Arthropoda) in rice and vegetable fields in a north-eastern district of Tamil Nadu, India - Anbalagan, Veeramuthu; Paulraj, Michael Gabriel; Ignacimuthu, Savarimuthu (Journal of Research in Biology, 2013)
Odonata diversity in vegetable fields (brinjal and okra) and rice fields was studied from January 2005 to December 2008 in Tiruvallur district of Tamil Nadu. Totally 23 species of Anisoptera (dragonflies) and 12 species of Zygoptera (damselflies) were recorded and all these species were grouped into eight families. In vegetable fields 31 species of dragonflies and damselflies were recorded under 22 genera. In rice fields the species richness (21 species) and total genera (16) were less than vegetable fields during the entire study period. Libellulidae was the large family in both vegetable and rice fields which comprised maximum number of species. Pantala flavescens (Fabricius), a migratory species, was the most dominant in numbers throughout the year. Diversity indices clearly showed that odonata diversity was higher in vegetable fields than in rice fields.